Queen Eleanor, independent spirit of the Medieval world : a biography of Eleanor of Aquitaine - Brooks, Polly Schoyer (New York : J.B. Lippincott, 1983)
A biography of the twelfth-century queen, first of France, then of England, who was the very lively wife of Henry II and mother of several notable sons, including Richard the Lionhearted.
Includes index.
Bibliography: p. [171]-172.
Keywords: Eleanor, -- of Aquitaine, Queen, consort of Henry II, King of England, -- 1122?-1204 -- Juvenile literature; Eleanor, -- of Aquitaine, Queen, consort of Henry II, King of England, -- 1122?-1204.; Queens -- France -- Biography -- Juvenile literature; Queens -- Great Britain -- Biography -- Juvenile literature; Kings, queens, rulers, etc